The Existence of Career Women in Egypt from a Social Cultural and Economic Perspective - Mariam Elbanna (Walidem Institute and Publishing, 2025)
Objective: This research explores the existence of career women in Egypt from social, cultural, and economic perspectives. The study aims to understand the challenges and opportunities faced by women in the workforce, highlighting factors influencing their career progression. Theoretical framework: The theoretical framework is grounded in gender equality concepts, social role theory, and the influence of patriarchal culture on women's workforce participation. Literature Review: The literature review encompasses previous studies on gender discrimination, work-family dynamics, and inclusive policies supporting career women, particularly in Middle Eastern countries. Methods: A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews. The survey involved 300 women, while in-depth interviews were conducted with 30 participants selected based on their diverse employment sectors and social backgrounds. This approach provided a comprehensive understanding of the challenges faced and opportunities available to career women in Egypt. Results: The results revealed that supportive workplace environments and family backing significantly enhance women's career advancement. Additionally, most participants emphasized the need for improved policies promoting gender equality in the workplace, including flexible work arrangements and access to professional training programs. Despite progress in women's participation across various sectors, barriers such as societal expectations, gender-based discrimination, and work-life balance challenges persist. Implications: The implications of this research underscore the importance of adopting gender-equality policies, cultural reforms, and empowering women through education and workforce training. This study provides a significant contribution to understanding the complexities surrounding women in Egypt’s workforce. Novelty: The novelty of this research lies in its integrated analysis of social, cultural, and economic factors, offering a holistic perspective on the experiences of career women in the country. It also highlights the need for a synergy between policy reforms and cultural shifts to create more inclusive work environments. In conclusion, while there has been progress in recognizing and supporting career women in Egypt, ongoing efforts are necessary to address existing gaps. These efforts should include progressive policies and cultural paradigm shifts to sustainably empower women and enhance their participation in the workforce.